2021
DOI: 10.3389/fgene.2021.785839
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Related Long Non-Coding RNA Signature Contributes to the Prediction of Prognosis Outcomes in Head and Neck Squamous Cell Carcinomas

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is a malignant tumor, which makes the prognosis prediction challenging. Ferroptosis is an iron-dependent form of non-apoptotic regulated cell death, which could affect cancer development. However, the prognostic value of ferroptosis-related long non-coding RNA (lncRNA) in HNSCC is still limited.Methods: In the current study, we employed the DESeq2 method to characterize the differentially expressed ferroptosis-related genes (FEGs) between cancer and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Studies have shown that lncRNA is abnormally expressed and regulated in a variety of tumors (Castro-Oropeza et al, 2018). It has been reported that abnormal lncRNAs can be used as prognostic indicators of various cancers (Ai et al, 2020;Gai et al, 2020;Jiang et al, 2021). At present, there are few studies on cuproptosis-related lncRNAs and their association with the prognosis of HNSC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that lncRNA is abnormally expressed and regulated in a variety of tumors (Castro-Oropeza et al, 2018). It has been reported that abnormal lncRNAs can be used as prognostic indicators of various cancers (Ai et al, 2020;Gai et al, 2020;Jiang et al, 2021). At present, there are few studies on cuproptosis-related lncRNAs and their association with the prognosis of HNSC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In cell lines of non-small cell lung cancer, it is transcriptionally activated, which is responsible for the inhibition of cell proliferation or induction of apoptosis [ 48 ]. However, in 2020 and 2021, two studies were conducted, demonstrating its importance also in HNSCC [ 49 , 50 ]. SFTA1P has potential prognostic significance and can be used to assess survival outcomes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…On this groundwork, in tumoral and normal tissue-derived exosomes, their team discovered a distinctive expression level of miR-4443 between cisplatin-sensitive and cisplatin-resistant tissues and cell lines, and further functional and bioinformatics studies confirmed that m 6 A writer METTL3 was negatively regulated by miR-4443 overexpression to lower the m 6 A level on ferroptosis-suppressing protein 1 (FSP1), inhibiting its activity to suppress ferroptosis. Bioinformatics analyses on lncRNAs also revealed m 6 A regulators, namely, FMR1, HNRNPC, METTL16, METTL3, and METTL5, were expressed in higher levels than those in ferroptosis low-risk groups ( Jiang, W. et al, 2021a ). The aforementioned studies provided evidence that epitranscriptomics are phenomenally involved in ferroptotic disease models, particularly in drug-resistant cancers that have the characteristic to overcome cell death events.…”
Section: Ferroptosis and Epitranscriptomics: Neither Two Monologues N...mentioning
confidence: 97%